Tathwîr al-Rusûm al-Hazliyyah al-Raqmiyyah 'alâ Tathbîq Canva li Ta'lîmi Mahârati al-Qirâah Ladâ Thullâbi al-Madrasati al-Ibtidâiyyah al-Islâmiyyah bi Indonesia - Tiara Sabilla; Toto Edidarmo; Fudhaili, Achmad; Shahid Seif al Din; Jawhar Youssef (IAIN Madura, 2025)
This research aims to develop digital comics using the Canva application to teach reading skills, assess their validity, and analyze students’ interests and responses. The study employed the ADDIE model of research and development, consisting of analysis, design, development, implementation, and evaluation stages. Data were gathered through observations, interviews, and validation questionnaires from experts and students and analyzed using percentages and a Likert scale. Results showed that the educational medium was highly effective, receiving scores of 87.6% from subject experts and 84% from media experts, categorized as